(untitled) (Texas Journal of Engineering and Technology, 2023)
The manner of seismic elements made of Ultra-High Performance Fiber Reinforced Concrete (UHPFRC) differs significantly from conventional concrete. However, limited research exists in the literature on the dynamic manner of UHPFRC seismic members due to their high cost. Limited element programs can reduce the need for experimental studies to develop design procedures for large-scale seismic elements. Validated analytical models can be utilised to investigate the impact of geometric changes, loading schemes, and reinforcement ratios on the seismic behaviour. This research employed a limited element program, specifically ABAQUS, to model a UHPFRC beam subjected to dynamic loading and evaluate the predictive accuracy of the numerical model. The material model parameters were determined based on uniaxial pressure and tensile tests. The findings from the numerical models demonstrate that the analytical model effectively predicts the dynamic behaviour of UHPFRC beams.